Pengaruh Beban Kerja dan Motivasi terhadap Kepuasan Kerja Karyawan Divisi Operasional PT. Siam Maspion Terminal - Azel Azahra Pramudita; Heru Baskoro (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee job satisfaction is an essential dimension in a company's personnel management system, particularly in the port services sector, which is characterized by high-demand work, fast-paced work rhythms, and complex operational dynamics. An optimal level of job satisfaction can have a direct impact on productivity, service quality, and the sustainability of the company's operations. PT. Siam Maspion Terminal, as a port company, focuses on managing its Operational Division by considering two main factors: workload and employee motivation, which are believed to play a significant role in determining the level of job satisfaction. This study aims to empirically examine the relationship between workload and motivation on employee job satisfaction in the Operational Division of PT. Siam Maspion Terminal. The research method used is quantitative with a survey design, involving 58 respondents selected using a census technique. Data were collected through a structured questionnaire that has been tested for validity and reliability, then analyzed using multiple linear regression with the help of SPSS version 26 software. The results of the study indicate that workload and motivation simultaneously and partially have a positive and significant effect on employee job satisfaction. This means that proportionally managed workload and effectively designed motivation can increase employee job satisfaction in this sector. These findings provide practical implications: company management needs to implement a fair, realistic, and balanced workload management strategy, accompanied by a structured, consistent motivation program tailored to employee needs and characteristics. This research is limited to the port services sector; therefore, it is recommended that similar research be conducted in other industrial sectors to gain a more comprehensive understanding and generalize the findings more broadly.